Estimation of stature from anthropometry of hand: an interesting autopsy based study in Madhya Pradesh, India - Goswami, Rajesh Ban; Thakur, P. S.; Dadu, S. K.; Rastogi, A. K. (International Journal of Research in Medical Sciences, 2017)
Background: Height of a person is an important parameter for the identification. Height or stature estimation is central dogma in anthropo-forensic examination. The human hand, which is the most used and versatile part of the body is of great scientific importance to investigators in the field of anthropometry, forensic pathology, orthopedic surgery and ergonomics. The hand length was found to be the most reliable alternative that can be used as a basis for estimating age-related loss in height. The hand length could also be used to predict body weight status and body surface area independent of the sex of the individual. Methods: The present cross sectional prospective study was carried out in mortuary of department of Forensic Medicine, Mahatma Gandhi Memorial Medical College and M.Y. Hospital, Indore (M.P.), India during study period from September 2014 to September 2015. The study was conducted on 250 deceased male and 250 deceased female individuals. The measurements were taken using standard anthropometric measuring instruments in centimeters to the nearest millimeters. All the measurements were recorded on a predesigned pretested proforma. Anthropometric measurements were taken as per the standard protocol. Results: The mean age of the male and female study subjects was38.472±13.28 years and 34.728±10.33 years respectively. Male to female ratio was 1:1. Mean stature in male subjects was 163.5±5.21 cm. Mean stature in female subjects was 155.69±10.12 cm. In male study subjects, mean hand length on right side was more than mean hand length on left side. In female study subjects, mean hand length on right side was more than on left side. In male study subjects, hand breadth (HB) on right side was more than on left side. Average HB in male subjects was 8.39±0.203 cm. In female study subjects, hand breadth on right side was more than on left side. Conclusions: The findings of the present study can be used as baseline information for other population based studies in the study area.